The journey from unmet need in allergic rhinitis to rationale for, and clinical development of, a new treatment option, MP29-02. (July 2014) - Bachert, Claus; Cardell, Lars-Olaf
The aim of allergic rhinitis treatment is to control symptoms, but currently considered first-line therapy provides suboptimal symptom relief for many patients. MP29-02 is a new treatment for allergic rhinitis, developed to fill this unmet need. Moderate/severe seasonal allergic rhinitis patients treated with MP29-02 experienced twice the nasal and ocular symptom relief as those treated with azelastine or fluticasone propionate. The effect was consistent across seasons, symptoms and by severity. MP29-02 delivered substantial and complete response in more patients and many days faster than fluticasone propionate or azelastine. Its efficacy advantage over fluticasone propionate extended beyond 14 days, up to 1 year, in chronic rhinitis patients. MP29-02 was well tolerated, both short and long term, and may change the way allergic rhinitis is managed, for the better.